PERLINDUNGAN-HUKUM-PEMEGANG-MEREK-TERKENAL TERHADAP-PELANGGARAN-MEREK UNTUK MEMBANGUN KEPASTIAN DALAM KEGIATAN PERDAGANGAN DI INDONESIA - Faizin Rahmadi Akbar (Jurnal HUKUM BISNIS, 2023)
To have the status-of a well-known mark, a brand-requires a lot of effort and time, even after the brand has the status-of-a well-known-mark, more efforts are still needed to legally protect the well-known-marks. Trademark infringement is a problem that--has-been rampant and is highly avoided by trademark owner, especially well-known mark, because the consequences of trademark infringement can be detrimental to the well-known mark owners themselves. This-research uses-normative research-methods. The results-of the-study show-that legal remedies that can-be-taken by well-known-mark-owners are to file a claim for compensation and a lawsuit-for cancellation-or deletion-of a-mark to the Commercial-Court, but the owner-of a-well-known mark does not necessarily receive a refund of the value of the loss according to the loss. Keywords: Well-Known Marks, Trademark Infringement, Legal Protection.